Influencing factors for recurrence after intermittent exotropia surgery - WANG Ya-chen, ZHANG Wei-jia, FU Tao (Jichu yixue yu linchuang, 2022)
Surgical operation is the most commonly used method to correct intermittent exotropia(IXT), and the results are relatively positive. However, after surgery, some patients will experience a recurrence of exotropia. The recurrence rate increases with time. At present, there is no unified conclusion on the factors in the recurrence after intermittent exotropia surgery. Age at onset and surgery, preoperative and initial postoperative deviation, abnormal visual function, type of intermittent exotropia, operation pathway and preoperative assessment method may all be the risk factors. This review presents a conclusion on different results of recent studies and indication of the interaction among factors in order to gain a better understanding of the surgical indication and provide guidance for future research directions.